The Building of A’Famosa Malacca on The Ruins of The Grand Mosque of Melaka – Based on Historical Records - Noor Aisyah Mokhtar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Melaka Sultanate Kingdom through its long centuries ruling must have majestic civilisation as lots of historical records by Europeans voyagers mentioned the great and powerful kingdom of Melaka during the Melaka Sultanate Empire - especially its Grand Mosque. Despite the many records of the mosque, its existence was still doubtful and questionable because there was no clear or obvious physical evidence that can be used as a basis support to the legitimacy of its existence. Thus, this study aims to uncover and identify historical evidence which state the validity of the its existence. The scope of this study focuses only on the physical building (which is believed to be historical evidence) of the Grand Mosque that historically believed was once built at the foot of Melaka Hill next to Melaka River. The method focused on this paper is through historical sources, previous studies as well as relevant scientific records. This research stated that the mosque indeed exists in historical writing and drawings, and was a square in geometry that fits in the philosophy and basic design of a mosque which after Portuguese conquisation - a fort was built on its ruins that known as A’Famosa. In conclusion, the Grand Mosque of Melaka once existed and mentioned in both historical records and drawings where later the famous A’Famosa Fort was built on its site and ruins. This study can be a catalyst for continuous and deeper research in the future on the original site and design of Grand Mosque.